Knowledge Management: Present Preview - SUBEDI, SAGAR RAJ (TULSSAA Journal, 2006)
This article shows Knowledge Management as a newly introduced genre in the field of Library and Information Science. This article further illustrates what really the Knowledge Management phenomenon is, its salient features as well as its need and significance in this age of information explosion. It exposes why a Library being a storehouse of knowledge, needs expert manpower at managing this ever-growing resource. It also differentiates between the first and second generations of Knowledge Management concepts. TULSSAA Vol.4(3) 2006 pp.1-3